Caesarean section and gastrointestinal symptoms, atopic dermatitis, and sensitisation during the first year of life. Issue 11 (21st October 2004) - Laubereau, B; Filipiak-Pittroff, B; von Berg, A; Grübl, A; Reinhardt, D; Wichmann, H E; Koletzko, S
Abstract : Aims: To investigate the effect of caesarean section on gastrointestinal symptoms, atopic dermatitis, and sensitisation to nutritional allergens in infants. Methods: A total of 865 healthy full term neonates with parental history of allergy participating in the prospective German Infant Nutritional Intervention Program (GINI) were exclusively breast fed during the first four months of life and had a one year follow up. Data were obtained by follow up visits at age 1, 4, 8, and 12 months, weekly diaries for the first six months, and measurement of total and specific IgE at birth and 12 months. Results: Infants born by caesarean section (147/865, 17%) had a greater risk of diarrhoea (ORadj 1.46, 95% CI 1.022 to 2.10) and sensitisation to food allergens, both in adjusted (ORadj 2.06, 95% CI 1.123 to 3.80) and stratified analyses (by cord blood IgE). Caesarean delivery was not associated with colicky pain and atopic dermatitis. Conclusion: Caesarean delivery might be a risk factor for diarrhoea and sensitisation in infants with family history of allergy. Further research in this area seems warranted as choosing caesarean section becomes increasingly popular.